The Development of a Portfolio for Academic Promotion and Tenure for Occupational Therapy Educators - David LeVan (Scholarworks @ WMU, 2020)
Advancement of occupational therapy educators is a significant achievement and important contribution to the American Occupational Therapy Association's Vision 2025 and Centennial Vision. Successful promotion demands excellence and active engagement in faculty skill development, both of which are essential to student learning. The academic promotion and tenure process presents a new and unfamiliar expectation for entry-level and tenure-track occupational therapy educators. A multitude of institutional policies and procedures, formal and informal recommendations from administrators and colleagues, and lack of mentorship can make planning for academic promotion and tenure confusing and difficult. The purpose of this article is to provide guidelines and practical examples based on evidence from higher education and the occupational therapy profession that can assist in the preparation and composition of a portfolio for academic promotion and tenure. Through appraisal and application, a portfolio can successfully present a record of quality teaching, advising, scholarship, professional development, and service while highlighting the distinct value of occupational therapy practice.